Neuroendocrine tumor of the gall bladder: A rare case report with review of literature - James R. Marak, MBBS, MD; Tushant Kumar, MBBS, MD; Shivam Dwivedi, MBBS; Rohini Khurana, MBBS, MD (Radiology Case Reports, 2023)
Neuroendocrine tumor of the gall bladder is an extremely rare malignancy, accounting for only 0.2% of all neuroendocrine tumors. Gall Bladder-Neuroendocrine Tumors (GB-NETs) are mainly diagnosed on histological examination of GB samples after cholecystectomy or after any biliary pathology surgery since it is very difficult to diagnose based on imaging. The overall outcome of gallbladder NET is worse than the adenocarcinoma of the gallbladder. No focused approach towards its treatment is available in literature due to its rarity. We share our experience of gall bladder NET in a 37-year-old female who was successfully managed at our institution.